Draft Sixth Five Year Plan 1980-85 Volume-II Government of Arunachal Pradesh - Planning Commission (Planning Commission, 1980)
The objective of the Agricultural Planning is to increase the production of cereals and the output of commercial crops with, a view to generating surplus and enhancing the purchasing capacity of the people and consequently raise their level of consumption further sustaining agro based industries in the secondary sector at household village level ultimately improving the socio-economic condition and the life and living of ‘the rura1 people.
Planning and Development Department